NALYSIS OF PROMOTION MIX IN SUMEDANG CAFÉ (COMPARATIVE STUDY OF SARVARA COFFEE AND DEJUE COFFEE) - Wulandari, Ghaidha Ayu; Kurniawan, Ryan Feryana; Damayanti, Wulan Ariani (Journal of Bussines Management Basic, 2025)
The promotion mix is used to find out how the promotion process is carried out to achieve the targets set by the company. This study aims to determine and analyze the promotion mix in Sarvara Coffee and Dejue Coffee in facing obstacles in implementing the promotion mix. The method used is qualitative with purposive sampling technique. With 18 informants. The results of the study show that Café Sarvara Coffee and Dejue Coffee Sumedang implement a promotion mix using advertising, sales promotion, word of mouth, personal selling, public relations and direct marketing. The conclusion of this study is that Café Sarvara Coffee Sumedang must expand the reach of promotions carried out by utilizing more creative and interactive promotion techniques and Dejue Coffee must increase the effectiveness of its promotion mix.